Pendugaan Daya Gabung dan Heritabilitas Komponen Hasil Tomat pada Persilangan Dialel Penuh - Saputra, Helfi Eka; Syukur, Muhamad; Aisyah, Syarifah Iis (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACT Hybridization is one of plant breeding techniques to obtain high yielding varieties. Combining ability and heritability information are needed for evaluating hybrids’ performance. The objective of this research was to estimate the combining ability and heritability of tomato yield component traits in a full dialel crosses at lowland. The experiment was conducted at Leuwikopo Experimental Station IPB, Darmaga, Bogor from March until August 2013. The random model of Griffing method I was used to estimate general combining ability, specific combining ability and heritability. The experiment used a randomized complete block design (RCBD) with three replications. IPBT1, IPBT13 and IPBT84 had a good general combining ability (GCA) for weight per fruit, fruit size and weight of fruit per plant. IPBT30 and IPBT33 had a good general combining ability (GCA) for number of fruits per plant. IPBT13 × IPBT1 hybrid showed a high and positive specific combining ability (SCA) values for all characters, therefore it can be used for hybrid variety. The highest broad and narrow sense heritability was obtained for fruit size, meanwhile the lowest was obtained for weight of fruit per plant. Weight per fruit, fruit size and weight of fruit per plant characters were influenced by additive and dominant gene effects, whereas number of fruit per plant was influenced by additive gene effects. Keywords: additive, dominant, GCA, SCA, heritability